(untitled) (Nóema, 2019)
After declaring that the reduction of the sartrean thought to simplified hermeneutical schemes cannot be considered as suitable anymore, the essay outlines the theme of singularity as a red thread that bind those writings, appeared during the ’50 and the ’70, where Sartre declares he would revise domain and method of a Marxist anthropology. The theoretical core of those writings is represented by the Critique of the Dialectical Reason. In its Foreword, previously published as Search for a Method, Sartre states that existentialism could play a major role in giving Marxism a methodological consistency and leading it to be founded as a rigorous historical materialism. The core of the Being and Nothingness ontological project is given by the notion of «human reality», which is an «anthropologically» radicalized version of the heideggerian Dasein. Taking inspiration from Heidegger, but nonetheless modifying his premises, Sartre gives to «human reality» a specific materialist trait, conceiving it as organic lack. In this way, the Marxist schemes of intelligibility of the historical and material processes could be reconsidered taking into account the «human reality»’s contingent nature. This is what pushes Sartre towards a revision of the dialectics, opening it to the comprehension of the singularity of everyone and to a historical knowledge that could finally aim to reach a true concreteness.